Current Population Survey, October 1981 ([Verlag nicht ermittelbar], 1984)
This data collection supplies standard monthly labor force data for the week prior to the survey. Comprehensive information is given on the employment status, occupation, and industry of persons 14 years old and older. Additional data are available concerning weeks worked and hours per week worked, reason not working full-time, total income and income components, and residence. Besides the CPS core questions, this survey also gathered supplemental data on school enrollment for all persons three years old and older. Data include whether the child attended public or private school, grade level, if enrolled in school after the age of 14, and, for persons 14-34 years old, year of high school graduation or last year attended school if a nongraduate. College students indicated whether they were enrolled in a two- or four-year program, as well as the type of degree anticipated. Those working toward associate's degrees specified if the program was occupational or general. College-age persons not attending college indicated whether they were taking any business, vocational, technical, or correspondence courses other than job training. Information on demographic characteristics, such as age, sex, race, marital status, veteran status, household relationship, and Hispanic origin, is available for each person in the household enumerated.